Percepções e conhecimento de profissionais e usuárias do sexo feminino que atuam na Atenção Primária de Saúde sobre relações de gênero - Leandro Genuir de Assis Caetano (2020)
The World Health Organization (WHO) has recognized gender violence as a public health problem specifically in Brazil, but also worldwide since 1990. Violence blatantly offends human rights and women's dignity. Multiple forms of violence, including femicide--the last stage in the cycle of violence against women, defined as the murder of women as a result of domestic violence or gender discrimination--are dictated by a patriarchal, macho, sexist and misogynistic society; in contexts marked by gender inequality; and predomin antly most times in a private setting, in which the aggressor knows the victim and attacks her for the sole reason she is a woman. The data on these violent acts published worldwide are of great magnitude, especially in Latin America and the Caribbean. The objective of this work is to evaluate the perception and knowledge of users and professionals of Primary Health Care in Belo Horizonte about the interfaces in gender relations due to the victimizing of women’s experience from of some type of violence, highlighting its characteristics and risk factors. As a methodology, an exploratory and descriptive study with both a qualiquantitative and qualitative approach was carried out through semi-structured interviews with users (interviewer) and professionals (self-applicable) of 45 Basic Health Units (BHU) of Primary Health Care in Belo Horizonte: randomly selected and distributed in the 9 Health Districts of Belo Horizonte in 2017. For the present study, only data referring to responses from female professionals and users were used. The statistical analysis was based on tables with absolute frequencies and percentages of univariate and bivariate distributions, in addition to Likert and boxplot bar graphs. An indicator, (IRGP) the Index of Positive Gender Relations, was constructed to quantify the level of gender relations in terms of their violent and non-violent characteristics, according to the conception of users and professionals. The questionnaires were answered by a total of 830 female users and 848 female health professionals. The IRGP indicator was categorized as low and, high using the median value as a cutoff point, which in the present, study was higher among professionals--the IRGP median numerical value was 70.5 in the user database and 75.0 in the professional database. The higher the IRGP, the better (positive) women's perception of gender roles. The median IRGP was found to be the highest for professionals who suffered violence in all the districts of Belo Horizonte. It is noticeable that these professionals had better perceptions of the group of items that make up gender relations, when compared to the group of users. Both groups showed a significant portion of victims of verbal, psychological/moral, physical, and bullying (intimidation) violence. We noted that both groups analyzed had an important percentage of women with a low IRGP, thus requiring a change in posture of women in the face of macho and patriarchal attitudes still seen in contemporary society.